Validation of the Mathematics Motivation Questionnaire (MMQ) for secondary school students - Logan Fiorella; So Yoon Yoon; Kinnari Atit; Jason R. Power; Grace Panther; Sheryl Sorby; David H. Uttal; Norma Veurink (SpringerOpen, 2021)
Abstract Background Motivation is critical for supporting persistence and achievement in science, technology, engineering, and mathematics (STEM) disciplines. In this study, we focus on the assessment of mathematics motivation among secondary school students. We provide validity and reliability evidence for the Mathematics Motivation Questionnaire (MMQ)-adapted from the Science Motivation Questionnaire designed for college students-using data from 2551 secondary students from seven states across the United States. Results Exploratory and confirmatory factor analyses confirmed five latent factors of the MMQ indicated by 19 items: intrinsic value, self-regulation, self-efficacy, utility value, and test anxiety. The nonlinear SEM reliability coefficients of the five constructs ranged from 0.76 to 0.91. To assess criterion validity, analyses using a subset of the data that included students' mathematics standardized scores (n = 536) indicated that intrinsic value, self-regulation, and self-efficacy were significantly positively correlated with mathematics achievement, whereas test anxiety was significantly negatively correlated with mathematics achievement. Conclusions The MMQ provides a reliable, valid, and feasible measure of the specific factors underlying mathematics motivation among secondary students.